The "ACT-ive" pursuit of loss and gain : the impact of an acceptance and commitment therapy-based intervention on post weight-loss surgery individuals : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Auckland, New Zealand - Damnjanovic, Natalija (Massey University, 2021)
Obesity prevalence continues to increase at an alarming rate worldwide and poses serious health risks to those affected including increased morbidity, mortality, and psychosocial consequences. Weight-loss surgery is currently the best evidence-based treatment for obesity yet, substantial postoperative weight regain is reported within 2-5 years. Successful weight management is complicated when longstanding psychological difficulties are present, that often require psychological input to address. In response, a private weight-loss surgery clinic has developed an Acceptance and Commitment Therapy-based (ACT) Intervention entitled the Foundations of Healthy Living (FOHL) Retreat with the aim of improving weight-loss surgery outcomes by providing greater support to individuals in the post-operative period. In this thesis, an exploration of the efficacy of the FOHL Retreat is conducted. A quasi-experiment pretest posttest non-equivalent control group design is utilised to investigate the impacts of the intervention on weight-related experiential avoidance, eating behaviour, and body mass index (BMI) over time. An additional supplementary exploration into participants’ relationships with food, eating, and their bodies pre- and post-surgically is undertaken using open-text response format questions. Those who attended the Retreat were also asked to share their perspectives on how their participation in the intervention affected their psychological wellbeing. The main findings of the study showed that the ACT-based intervention demonstrated significant effects on several of the variables of interest, in particular, disordered eating and BMI. These effects were mediated by improvements in weight-related experiential avoidance, suggesting the importance of focussing on targeting experiential avoidance as a key mechanism of change in positive postoperative psychological and weight outcomes. The qualitative component of this study expanded on these findings, identifying several key themes present in the experiences of individuals both prior to, and following, weight-loss surgery. Additionally, qualitative responses provided further insight as to the psychological changes participants experienced. Taken together, these findings highlight firstly, the importance of addressing the psychological needs of weight-loss surgery individuals, and secondly, the value of ACT in augmenting surgical outcomes. The results presented here also offer suggestions for further development and future dissemination of such interventions for this population.
Keywords: Acceptance and commitment therapy; Obesity; Surgery; Patients; Weight loss; Psychological aspects; New Zealand; Auckland; 520399 Clinical and health psychology not elsewhere classified